ARIAS Learning Model (Assurance, Relevance, Interest, Assessment, Satisfaction) And Their Effect on Madrasah Tsanawiyah Student Creativity - Iim Siti Aminah; Arif Muchyidin; Reza Oktiana Akbar (Journal of General Education and Humanities, 2022)
This study aims to determine students' creativity ability using model ARIAS. This study uses quantitative research with an experimental method, with the entire population of students of class VIII MTs Sabilul Chalim Leuwimunding, as many as 136 students. The sample in this study using cluster random sampling was divided into two groups: VIIIC class as the control class with a total of 34, and VIIID class as a class experiment with several students as many as 34 students—research analysis using linear regression. The results showed that students' response to learning by using a model of ARIAS has a strong category with an average of 75.6%, and the creativity of students with models categorized ARIAS as more than enough for the average post-test score of 75.26. In contrast, students' creativity using conventional methods (lectures) was organized less, with an average of 62.97, and the third use of the learning model ARIAS positively affected students' creativity by 20.7%.